Research Progress in Fatigue of Honeycomb Sandwich Panels - Ma Mingze; Yao Weixing; Chen Yan (Hangkong gongcheng jinzhan, 2019)
Honeycomb sandwich panels have become more and more widely used in the aerospace field, and the fatigue problems that occur during their application have become increasingly prominent. At present, there is little research on the fatigue of honeycomb sandwich panels, and the test methods used in the study are also very different. Under different test methods, the fatigue process of Nomex honeycomb sandwich panels varies greatly. This article mainly reviews the research progress of the fatigue of honeycomb sandwich panels. The purpose is to compare the fatigue damage process of honeycomb sandwich panels under different test methods and summarize the similarities and differences of the fatigue performance of honeycomb sandwich panels. By introducing the fatigue test method, fatigue damage process, fatigue life prediction method and fatigue life curve of honeycomb sandwich panel, the research direction of the fatigue of honeycomb sandwich panel is proposed.